Influence of phosphoproteins' biomimetic analogs on remineralization of mineral-depleted resin–dentin interfaces created with ion-releasing resin-based systems. Issue 7 (July 2015) - Sauro, Salvatore; Osorio, Raquel; Watson, Timothy F.; Toledano, Manuel
Graphical abstract